Utilizing recycled glass powder in reinforced concrete beams: comparison of shear performance - Memduh Karalar; Boğaçhan Başaran; Ceyhun Aksoylu; Özer Zeybek; Essam Althaqafi; Alexey N. Beskopylny; Sergey A. Stel’makh; Evgenii M. Shcherban’; Osman Ahmed Umiye; Yasin Onuralp Özkılıç (Scientific Reports, 2025)
Abstract In this research, the effect of using waste glass powder (WGP) as a partial replacement for cement on the flexural behavior of reinforced-concrete-beams (R-C-Bs) was investigated. For this aim, a total of 9 specimens were produced, and investigational experimentations were conducted to evaluate the flexural performances of R-C-Bs. Subsequently, the cement was partially replaced with WGP with weight percentages of 0%, 10%, 20% and 30%. Furthermore, the influence of stirrup spacing (SS) in the longitudinal reinforcement on productivity was also examined. The results presented indicate that the efficient WGP percentage might be considered as 10% of the partial replacement of cement. Increasing the WGP percentage within the cement by more than 10% may considerably reduce the ability of the R-C-Bs, noticeably when the lengthwise reinforcement proportion is high. Additionally, the experimental shear strengths of R-C-Bs attained from the flexural tests were compared with the shear capacities estimated using Eurocode 2 and ACI 318 − 19 regulations. It was concluded that the shear capacities calculated with ACI318-19 are much lower than the values calculated with EC2. Furthermore, it may be observed that ACI318-19 calculates the shear capacities of R-C-Bs to be 15–51% higher than those of the experimental results. Furthermore, the Digital Image Correlation (DIC) was used to study the flexural cracks/micro-cracks in R-C-Bs. Comparisons indicate that DIC has similar deformations and fracture properties for the R-C-Bs as the experimental tests. Finally, it was considered that the optimum consumption quantities determined by the results of the present research would be a guide for future investigation.